Mixing and Power Consumption of Structured Fluids in Stirred Reactors - Giuseppina Montante; Gianluca Boccardo; Nicola Antonio Di Spirito; Nino Grizzuti; Francesco Maluta; Daniele Marchisio; Alessandro Paglianti; Rossana Pasquino (Chemical Engineering Transactions, 2025)
This work deals with the fluid dynamics characterization of structured fluids, which are adopted in the preparation and processing of many products in different industrial applications. Experiments on binary mixtures of water and Pluronic L64 are carried out in a laboratory stirred reactor, by varying the mixture concentrations and the temperature, thus obtaining different microstructures of Pluronic molecules in water corresponding to different fluid rheology. The fluid dynamics characteristics are measured by Stereo Particle Image Velocimetry. The resulting data are presented and discussed with the final purpose of providing insight into the prevailing flow regimes, the velocity field and the shear rate in the reactor volume. In addition, power consumption measured by a strain gauge system allows to estimate the energy requirement expected in the industrial operations. The results show significant spatial variations of the velocity field and related variables. The data can be adopted for the improvement of the design and operation of the reactors and for the validation of a multiscale modelling methodology of the same systems.